Laser additive manufacturing of a 316L/CuSn10 multimaterial coaxial nozzle to alleviate spattering adhesion and burning effect in directed energy deposition. (October 2022) - Liu, Linqing; Wang, Di; Deng, Guowei; Han, Changjun; Yang, Yongqiang; Chen, Jie; Chen, Xiexin; Liu, Yang; Bai, Yuchao
Abstract: Multimaterial additive manufacturing is aimed at the integration of functionality and mechanical performance of dissimilar materials for various applications. In this work, a 316L/CuSn10 multimaterial coaxial nozzle was designed and additively manufactured by laser powder bed fusion (LPBF) for alleviating spattering adhesion and burning effect in directed energy deposition. The applicability of the 316L/CuSn10 nozzle was then validated in the laser-based directed energy deposition (L-DED) process. The interfacial diffusion zone of the 316L/CuSn10 structure was measured with a length of 400 μm, indicating a well bonding between 316L and CuSn10. A high laser power ( P = 230 W) and a low scanning speed ( v = 300 mm/s) adopted for printing CuSn10 on 316L could lead to "keyhole mode", resulting in a large penetration depth of the pre-solidified layer and wide diffusion zone at the interface. The spattering behavior of the 316L/CuSn10 nozzle applied in the L-DED process showed that the heterogeneity of dissimilar materials could reduce the adverse effect of the adhesion of spattering droplets. High laser reflection and high thermal conductivity of CuSn10 could relieve the burning effect of the reflected laser beam on the tip of the 316L/CuSn10 nozzle. Therefore, the utilization of CuSn10 on the nozzle tip could improve its service life. These findings may serve as a new way for low-cost and rapid mass production of the coaxial nozzles that can be applied in the L-DED technique.